Five‐year trend of antipsychotic prescription practices in a district Hospital in Ghana: A retrospective study - Dennis Bomansang Daliri; Agani Afaya; Timothy Tienbia Laari; Adiak Fredrick; Ama Gaynor Ankamah; Susana Annan; Nancy Abagye (Wiley, 2023)
Abstract Introduction Antipsychotics are the mainstay treatment for psychotic conditions. Their prescription, however, should come with some caution since the consequences of their side effects can be dire for the patient receiving the prescription. Because of inadequate experts in low‐middle‐income countries, non‐experts are trained through the Mental Health Gap Action Program (MHGAP) to reduce the treatment gap. This retrospective study analyzed the trend of antipsychotic prescriptions in a district hospital where mental health services are delivered by non‐experts. Methodology This was a retrospective descriptive study that gathered data between 2015 and 2019 from the electronic database of the hospital. Statistical analysis was conducted using SPSS version 20. We reported the descriptive statistics of our findings in the form of frequencies and percentages. Results There was a year‐on‐year increase in antipsychotic prescriptions over the study period. Starting with 48.1% in 2015 to 56.4% in 2019. The main condition for which antipsychotics were prescribed was psychosis (58.6%), followed by substance use disorder (SUD) (26%). Patients with age ≥ 50 received the most prescription of antipsychotics. Starting from 2015, there was a high percentage of typical antipsychotic prescriptions (90.14%) with atypical antipsychotics being 9.86% and by 2019 atypical antipsychotic prescriptions had shot up to 74.8%. Polypharmacy prescription rate was 8.1% over the study period. Conclusion Antipsychotics are essential in the treatment of psychosis and other mental health conditions. Prescribers need to know more about these drugs to prescribe them appropriately and to minimize the likelihood of side effects among patients who use these drugs.